Кореляційне виявлення об'єктів на основі моделей активних форм - Мандзій, Т.С. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
New correlation-based approach for object detection is proposed. Method for varying shape object detection is developed. Proposed method showed promising results on synthetic images.